Influence of C-Peptide on Glucose Utilisation. (27th March 2008) - Wilhelm, B.; Kann, P.; Pfützner, A.
Abstract : During the recent years, multiple studies demonstrated that C-peptide is not an inert peptide, but exerts important physiological effects. C-peptide binds to cell membranes, stimulates the Na, K-ATPase and the endothelial nitric oxide (NO) synthase. Moreover, there is evidence that C-peptide decreases glomerular hyperfiltration and increases glucose utilisation. Nevertheless, there is still limited knowledge concerning mechanisms leading to an increased glucose utilisation either in rats or in humans. The aim of this paper is to give an overview over the published studies regarding C-peptide and glucose metabolism from in vitro studies to longer lasting studies in humans.